Comprehensive Characterization of Neat Polymers and Compositional Imaging Heterogeneous Polymer Systems with AFM Based Mechanical, Electric and Spectroscopic Methods. Issue 1754 (27th February 2015) - Surtchev, Marko; Belikov, Sergey; Malovichko, Ivan; Magonov, Sergei
ABSTRACT: Comprehensive characterization of materials suggests measuring their different properties for optimal use in technological applications and this task becomes more challenging as size of related structures decreases and their complexity increases. At smaller scales Atomic Force Microscopy (AFM) enables visualization of structures and quantitative measurements of their mechanical and electric properties. So far, several properties such as elastic modulus and work of adhesion, surface potential and dielectric permittivity can be extracted from the results obtained in various AFM modes. More complicated are the AFM experiments and their analysis in case of viscoelastic, piezoelectric and thermoelectric properties. Several examples of quantitative characterization of neat polymers will be given. In many cases the dissimilarity of the components' properties is employed for their recognition in heterogeneous systems such as polymer blends, block copolymers and metal alloys. The confined geometries, which are common for small-scale structures, might restrict such identification and a combination of AFM with spectral methods such as Raman scattering will be helpful. Achievements and challenges of compositional mapping will be illustrated on several complex materials.